CREATING NEW GENERATION STANDARDS IN PROVIDING QUALITY OF MEDICAL EDUCATION - Gordiychuk, Svitlana (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the need to refresh educational content and establish new higher education standards framework according to the new Law "On Higher Education" in Ukraine. The author determines demands for the quality of scope, structure and educational outcomes defined by the education standards framework. The basic concepts “education standards framework", “education programme”, “competence”, “learning outcome” are analyzed in the paper. The advanced experience of creating education standards framework within subject area 22 – “Health Care”, specialty 223 “Nursing”, educational level Bachelor is generalized. This experience is based on the main principles of Competence-based approach and the concept of student-centered education. The standard structure includes: general characteristics, programme scope in ECTS, graduates’ list of competences, normative content of higher degree-seekers training, educational terms and results, higher degree-seekers’ assessment, requirements for the system of providing institutions’ internal quality of education, is defined. The special attention is payed to the subject area description (learning objective and activity objective, educational aims, theoretical scope of subject area, methods, methodology and technologies, instruments and facilities (object/subjects, devices to use). The general and special competences that form the future specialists’ professionalism and person individuality are thoroughly represented in the paper. The learning outcomes are presented in 3 main spheres: cognitive (knowledge, understanding, applying, analyses, synthesis, estimation), affective (perception, reaction, values, organization and conceptualization), psychomotor (imitation, manipulation, achieving accuracy level, combining, naturalization).